RGMa Participates in the Blood–Brain Barrier Dysfunction Through BMP/BMPR/YAP Signaling in Multiple Sclerosis - Lei Zhang; Shi Tang; Yue Ma; Junhang Liu; Philippe Monnier; Philippe Monnier; Philippe Monnier; Hang Li; Rongrong Zhang; Gang Yu; Mengjie Zhang; Yongmei Li; et al. (Frontiers in Immunology, 2022)
The infiltration of inflammatory cells into the central nervous system (CNS) through the dysfunctional blood–brain barrier (BBB) was critical in the early stages of MS. However, the mechanisms underlying BBB dysfunction remain unknown. Repulsive guidance molecule-a (RGMa) is involved in the pathogenesis of multiple sclerosis (MS), but its role needs to be further explored. This study aimed to evaluate whether RMGa regulates BBB permeability in endothelial cells and MS, and if so, what mechanism may be involved. We created an experimental autoimmune encephalomyelitis (EAE) model in C57BL/6 mice and a human brain microvascular endothelial cell (HBMEC) culture. The permeability of the BBB is measured in response to various interventions. Our results showed that RGMa is expressed in the endothelial cells in HBMECs and EAE mice. RGMa and its signaling counterpart, bone morphogenetic protein 2 (BMP2)/bone morphogenetic protein receptor type II (BMPRII), were gradually increased as the disease progressed. Moreover, as EAE progressed and the BBB was disrupted, the downstream effector, yes-associated protein (YAP), as well as the tight junctional proteins zonula occludens 1 (ZO-1) and claudin-5, decreased significantly. The permeability assay revealed that lentivirus-induced RGMa overexpression in HBMECs caused a significant breakdown of the BBB, whereas RGMa knockdown significantly strengthens the integrity of the BBB. Furthermore, specifically activating BMPR II or inhibiting YAP based on RGMa knockdown results in a significant decrease of ZO-1 and claudin-5 in vitro. On the contrary, inhibition of BMPR II or activation of YAP after upregulating RGMa prevents the downregulation of ZO-1 and claudin-5 in HBMECs. In addition, serum-soluble RGMa (sRGMa) levels were significantly higher in MS patients, particularly in MS patients with Gd+ lesions, indicating that the BBB has been disrupted. In conclusion, this study shows that RGMa causes BBB dysfunction in endothelial cells via BMP2/BMPR II/YAP, resulting in BBB integrity disruption in MS and that it could be a novel therapeutic target for BBB permeability in MS.